Myasthenia gravis therapy with individualized homeopathy: A case report - Văcăraș, Vitalie (Clin Case Rep, 2020)
We present a 61‐year‐old man with severe myasthenia gravis, nonresponsive to conventional therapy. The patient was treated with individualized homeopathy, demonstrating significant improvement on his clinical status and no disease symptoms.